Incidence and prognostic relevance of cardiopulmonary failure in takotsubo cardiomyopathy - El-Battrawy, Ibrahim; Lang, Siegfried; Ansari, Uzair; Sattler, Katherine; Behnes, Michael; Fastner, Christian; Tueluemen, Erol; Zhou, Xiao-Bo; Hoffmann, Ursula; Borggrefe, Martin; Akın, Ibrahim (Scientific reports, 2017)
Recent studies have indicated that patients with takotsubo cardiomyopathy (TTC) have a higher mortality rate than the general population. There is a distinct possibility that TTC could be associated with adverse life-threatening complications like cardiopulmonary failure. Our institutional database constituted a collective of 114 patients diagnosed with TTC. The frequency, determinants and predictors of cardiopulmonary failure were assessed. The patients were subsequently classified into two groups based on the presence (n = 44, 38.6%) or absence (n = 70, 61.4%) of cardiopulmonary failure. Multivariable logistic-regression analysis identified impaired left ventricular function defined as ≤35% at presentation and life-threatening arrhythmia as a positive significant independent predictor of cardiopulmonary failure. A majority of the patients with cardiopulmonary failure were treated with either non-invasive or invasive ventilator support (88%), while 48% of the patients required treatment with catecholamine. The in-hospital mortality rate was greater in the cardiopulmonary failure group. Cardiopulmonary failure patients were at ongoing increased risk of death with a higher mortality at 30-day, 1-year and at 5 years of follow-up. Cardiopulmonary failure is a frequent complication in TTC with an increased short- and long-term mortality. Patient susceptible to this condition could be identified by a reduced ejection fraction and life-threatening arrhythmia.
Gesehen am 06.04.2018